Empowering African-Canadian Career Excellence - Community Economic Development and Employability Corporation (CEDEC) (2019)
The African-Canadian Career Excellence (ACCE) initiative was developed to address the loss of highly-educated, English-speaking Black youth from the Greater Montreal Area (Quebec, Canada) facing issues of unemployment and underemployment.
Keywords: Official Language Minority Community (OLMC)

African-Canadian Career Excellence : 2015 Employer Survey - Community Economic Development and Employability Corporation (CEDEC) (2015)
This report provides the final data analysis and interpretation of the 2015 employer survey on the hiring norms and practices of businesses across various sectors and industries in the Greater Montreal area, with a focus on employers’ attitudes towards the importance of a having a diverse workforce. This study is part of the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal.

African-Canadian Career Excellence : Undergraduate Survey 2011-2012 Summary Report - Community Economic Development and Employability Corporation (CEDEC) (2013)
This summary report provides the final data analysis and interpretation of the 2011-2012 undergraduate student survey on perceptions of transition to employment in Montreal. As one step in the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal, this summary will inform the design of development training for young graduates to facilitate their career launch and advancement in Quebec. Information and insights herein were provided by the following members of ACCE: Dorothy W. Williams of the Black Community Resource Centre (BCRC), Dwight Best of the African and Caribbean Students’ Network of Canada (ACSioN), Tamara Hart of the Tyndale St-Georges Community Centre, Velda Bourne, Karima West, and Nina Kim and Larissa Milo-Dale of the Community Economic Development and Employability Corporation (CEDEC). Preliminary data analysis and interpretation were contributed by Jan Warnke J W COMM INC.

African-Canadian Career Excellence : 2014 Student Survey : The Needs and Challenges of Education Black Youth in Obtaining Meaningful and Sustainable Employment - Community Economic Development and Employability Corporation (CEDEC) (2015)

Business Vitality Initiative : Community Handbook - Community Economic Development and Employability Corporation (CEDEC) (2010)
If you’re not asking these questions, it’s unlikely you’re maximizing the potential of your community. Communities identifying their strengths, their gaps and their unexplored opportunities— that is what’s behind the BVI, a measurement and action process that helps communities harness their business potential. It has been designed to help communities assess their capacity to work with and support entrepreneurs, and to foster business growth. The BVI has been employed in communities across Canada (and recently in Australia) by a team based in Nelson, BC. The CIEL/BVI Team has been nominated for BC’s top award in community economic development and most recently won an award as the region’s most innovative organization. The BVI measures the perceptions of community leaders, business people and citizens about the current business environment in the community and compares the scores to those from other communities using a unique graphical index (the Business Vitality Index).

Business Vitality Initiative : Facilitator Handbook - Community Economic Development and Employability Corporation (CEDEC) (2010)
The Purpose of this Manual: The BVI includes two highly structured public meetings which require expert facilitation. This manual is a basic resource for facilitators. Other necessary resources include: • The BVI PowerPoint presentation • The BVI Community Handbook • Discussions with CIEL management • Discussions with the Community Sponsor • A BVI Assessment Report and Final Report from another community

Tourism 2025 : CEDEC's Plan for Creating 46,900 Jobs and Adding $5.2 Billion to the Economy - Community Economic Development and Employability Corporation (CEDEC) (2017)

Tourisme 2025 : Le plan de la CEDEC pour cré2r 46 9000 emplois et ajouter 5.2 milliards de dollar à l'économie - Community Economic Development and Employability Corporation (CEDEC) (2017)

Business vitality initiative : Manuel de l'animateur - Community Economic Development and Employability Corporation (CEDEC) (2010)
Le Business Vitality Initiative (BVI) comprend deux assemblées publiques très structurées qui doivent être animées par un expert. Le Manuel est la ressource principale des animateurs de ces assemblées, mais d’autres ressources sont aussi mises à leur disposition, notamment : • le diaporama sur le BVI; • le Manuel de la communauté – BVI; • le compte rendu des discussions avec la direction du CIEL; • le compte rendu des discussions avec l’organisme de parrainage communautaire; • un rapport d’évaluation dans le cadre du BVI et le rapport définitif d’une autre communauté.

Initiative pour l'excellence de la carrière des Afro-Canadiens : Enquête réalisée en 2014 : Les besoins et les défis auxquels font face les jeunes de race noire pour obtenir un emploi rémunérateur et durable - Community Economic Development and Employability Corporation (CEDEC) (2015)
Ce rapport présente l’analyse et l’interprétation de l’enquête réalisée auprès des étudiants du premier cycle universitaire en 2014 sur leurs perceptions de la transition vers l’emploi à Montréal. Ce résumé, une étape réalisée par l’Initiative pour l’Excellence de la carrière des Afro-Canadiens œuvrant à contrer la migration des jeunes diplômés noir montréalais, vise à influencer la conception de formations s’adressant aux jeunes diplômés afin de faciliter le lancement de leur carrière et la progression de celle-ci au Québec.

Initiative pour l'excellence de la carrière des Afro-Canadiens : Sondage réalisé auprès des étudiants du premier cycle universitaire - Community Economic Development and Employability Corporation (CEDEC) (2013)
Ce rapport sommaire consigne les résultats et l'interprétation de l'analyse des données du sondage réalisé auprès des étudiants au premier cycle universitaire de 2011-2012 sur leurs perceptions de la transition vers le marché du travail de Montréal. Comme l’une des démarches de l'Initiative pour l’Excellence de la carrière des Afro-Canadiens consiste à contrer la migration des diplômés noirs de Montréal, ce rapport influencera l'élaboration de formations de perfectionnement pour les jeunes diplômés afin de faciliter l’amorce de leur carrière et leur progression professionnelle au Québec.

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 12

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 9

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 13

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 15

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 4

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 4

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 5

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 7

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 6

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 6

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 12

Le magazine en ligne de la CEDEC : De meilleures économies pour de meilleures vies - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 13

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 9

Le magazine en ligne de la CEDEC : De meilleures économies pour de meilleures vies - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 10

[CEDEC Newsletter] - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 10

[CEDEC Newsletter] - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 11

CEDEC hopeful Official Languages Act Action Plan will have long-term impact and meaningful difference to ESCQ vitality - Community Economic Development and Employability Corporation (CEDEC) (2023)

La CEDEC a bon espoir que le plan d'action pour les langues officielles aura un effet à long terme et fera une importante différence sur la vitalité de la communauté d'expression anglaise du Québec - Community Economic Development and Employability Corporation (CEDEC) (2023)

Stanstead Dinner and Show series kicks off collaborative effort to increase local tourism - Community Economic Development and Employability Corporation (CEDEC) (2023)

Une série de dîners-spectacles donne le coup d’envoi à un effort collaboratif pour augmenter le tourisme local - Community Economic Development and Employability Corporation (CEDEC) (2023)

Economic Development and Community Vitality : A Report on Federal Funding Streams Available to the English-speaking Community of Quebec - Quebec Community Groups Network (QCGN); Community Economic Development and Employability Corporation (CEDEC); Youth Employment Services (YES) (2023)
The following report provides an overview of the main federal funding streams for the English-speaking community in Quebec (ESCQ) along with the French-speaking community in the rest of Canada. This includes an overview and analysis of the Canada Economic Development for Quebec Regions (CED-Q), including the Official Languages Economic Development Initiative (EDI) and other official language minority communities (OLMCs) specific funding streams: Regional Economic Growth through Innovation (REGI), the Quebec Economic Development Program (QEDP), and the Community Futures Program (CFP). As a means of comparing funding levels for the French-speaking community outside of Quebec, this study also reviews Canada Economic Development for the Rest of Canada (CED-ROC).
Keywords: Official Language Minority Community (OLMC)